2004
DOI: 10.1002/jcp.20150
|View full text |Cite
|
Sign up to set email alerts
|

Laser pressure catapulting (LPC): Optimization LPC‐system and genotyping of colorectal carcinomas

Abstract: Genotype analysis is becoming more and more useful in clinical practice, since specific mutations in tumors often correlate with prognosis and/or therapeutic response. Unfortunately, current molecular analytical techniques often require time-consuming and costly steps of analysis, thus making their routine clinical use difficult. Moreover, one of the most difficult problems arising during tumor research is that of their cell heterogeneity, which depends on their clear molecular heterogeneity. SSCP analysis dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
1

Year Published

2005
2005
2012
2012

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 17 publications
0
12
1
Order By: Relevance
“…Others have found that combining laser microdissection with sensitive molecular methods such as real-time PCR, previously unanswerable questions about the development and progression of human cancer can be explored [24][25][26]. Notwithstanding, in our study, the increased cyclin A2 protein expression could not be explained by CCNA2 amplification analyses in isolated colonic tumour cells.…”
Section: Discussioncontrasting
confidence: 49%
“…Others have found that combining laser microdissection with sensitive molecular methods such as real-time PCR, previously unanswerable questions about the development and progression of human cancer can be explored [24][25][26]. Notwithstanding, in our study, the increased cyclin A2 protein expression could not be explained by CCNA2 amplification analyses in isolated colonic tumour cells.…”
Section: Discussioncontrasting
confidence: 49%
“…Another way to increase tumor cell enrichment is to perform a more selective dissection of the scattered tumor cells/glands by laser capture microdissection. 17,30 In our hands, laser capture microdissection is efficient (two additional mutations were identified), but does not seem to be suitable for a routine setting because it is time-and laborconsuming and, therefore, expensive. In practice, 10-100 min were necessary for microdissecting a sample, depending on its tumor cellularity.…”
Section: Discussionmentioning
confidence: 89%
“…However, it is time-consuming and labor-intensive and yields less DNA than manual macrodissection [31]. …”
Section: Kras and Braf Mutations: Description And Detection Methodsmentioning
confidence: 99%